Implementasi Kebijakan Program Gerakan Daerah Angkat Anak Muda Putus Sekolah di Dinas Pendidikan Kabupaten Banyuwangi - Putranda, Dicky; Helpiastuti, Selfi Budi; Hara, Abubakar Eby (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
This research is closely related to the problem and is the direction of the answer from the hypothesis or a temporary description of the assumptions. Based on the formulation of the problem that has been stated, the goal to be achieved in this study is to analyze the implementation of the Regional Movement for Lifting Out-of-School Youth Program in Banyuwangi Regency. The Regional Movement Program to Raise School Dropout Youths is part of the Banyuwangi Regency Government's efforts to provide education to the community, especially school children who come from poor communities. The Regional Movement for Lifting Out-of-School Youth is an ideally good program, but it requires accuracy in implementing, utilizing and utilizing it by the community. If this can be done, then the results can have a positive impact on the development of Banyuwangi district in the future. Therefore, on this occasion the researchers conducted research with the title